EFEKTIVITAS MODEL RECIPROCAL LEARNING DALAM KEMAMPUAN MEMBACA PEMAHAMAN SISWA SD PADA PEMBELAJARAN BAHASA INDONESIA - Zulhaj Jusman; Aco Karumpa; Anzar (STKIP Subang, 2026)
This study aims to determine the effect of using the Reciprocal Learning model on students’ learning outcomes in reading comprehension in class V B of UPT SPF SD Inpres Minasa Upa 1, Rappocini District. The research employed an experimental method with a One Group Pretest-Posttest design, involving a saturated sample of 17 students. Data were collected through a reading comprehension test and analyzed using both descriptive and inferential statistical techniques, including tests of normality, homogeneity, and hypothesis testing. The findings revealed that the students’ average pretest score of 25.59 increased significantly to 90.59 in the posttest. A Paired Sample T-test indicated a significance value of < 0.001, leading to the rejection of H0 and the acceptance of H1. These results demonstrate that the Reciprocal Learning model is effective in enhancing students’ reading comprehension skills. Therefore, the implementation of this model has a positive impact on learning outcomes and may serve as a valuable reference for elementary school teachers in developing innovative instructional strategies to improve the quality of learning.